Body packer syndrome - Alkan, Nevzat (Journal of Dependence, 2004)
Despite the best efforts of the police to stop illegal drug smuggling, it cannot be entirely prevented. Smugglers change their methods and utilize new ones to overcome the improved and more effective methods used by the security forces. Since 1970, a new method was introduced for illegal drug smuggling: Carrying the drug inside body cavities. The body cavities used mostly are the gastrointestinal system between the mouth and anus, ears and vagina. The drugs carried by this method are primarily cocaine, occasionally heroin and rarely, marijuana. Smugglers could not be captured unless someone informs the authorities about the smuggling, the smuggler behaves suspiciously, or symptoms of drug toxicity appear. Drug packages may be dissolved by the digestive activity of enzymes especially in the gastrointestinal tract, their permeability may increase resulting in drug leakage. The signs of the resulting drug toxicity is called Body Packer Syndrome. Some general information will be given in the introduction of this article. Then, the principles of treatment of patients with Body Packer Syndrome will be explained. After that, we have attempted to review postmortem researches carried out on postmortem patients, the articles published in the international medical literature and national newspapers relating to the Body Packer Syndrome and discussed aspects of this smuggling method and important points to consider.